Checklist of aphyllophoroid fungi (Agaricomycetes, Basidiomycota) in boreal forests of Pinega Reserve, north-east European Russia - Ezhov, Oleg; Zmitrovich, Ivan (Check List, 2015)
Herein we present a checklist of aphyllophoroid fungi of the Pinega Reserve, in the territory of North European Russia. We present 328 species from 158 genera in the checklist. Each record includes data on distribution within key reserve localities, the host/substrate association and the frequency pattern. Most findings are documented by herbarium specimens. A predictive estimation of the Pinega Reserve aphyllophoroid diversity, based on Turing coefficient calculation, resulted in an interval of 360–370 species.